Psicanálise e feminismo : algumas reflexões sobre a mulher enquanto Outro - Mountian, Ilana; Lacorte Gianesi, Ana Paula (2020)
This article promotes a debate on otherness and gender in psychoanalysis, based on feminist theories. Feminism raises fundamental questions to psychoanalysis, requiring the revision of some of its principles - the cornerstones of its praxis - in order to expand psychoanalytical reading. While on the one hand, psychoanalysis exercises a challenging and engaged practice, on the other hand, a psychoanalytical practice without critical reflectivity may not consider the social context and the discursive effect of the position occupied by the subject. From feminist readings, psychoanalytical praxis (both theoretical and clinical) will be examined, shedding light on questions regarding gender issues, namely: the place of women (not-all/Other sex) and men (phallic) and the heteropatriarchy conjugated to it.
Este artigo promove um debate sobre alteridade e gênero na psicanálise com base em teorias feministas. O feminismo traz questões fundamentais à psicanálise, exigindo a revisão de alguns de seus pilares - sustentáculos de sua práxis -, e a ampliação da leitura psicanalítica. Se por um lado, a psicanálise segue contestadora e atuante, por outro lado, uma prática psicanalítica sem reflexividade crítica, pode desconsiderar o contexto social e o efeito discursivo da posição ocupada pelo sujeito. Assim, a partir de leituras feministas, interrogar-se-á a práxis (a um só tempo teórica e clínica) psicanalítica, colocando luz nos problemas que se revelam nos tratos com questões de gênero, a saber: o lugar da Mulher (não-toda/Outro sexo) e do Homem (Todo fálico) e o heteropatriarcado conjugado a este.
Keywords: Psychoanalysis; Feminism; Listening; Patriarchy; Other; Psicanálise^lpt; Feminismo; Escuta; Patriarcado; Outro